Effects of photobiomodulation on sport performance in swimming para-athletes - a case series - Garcez, A.; Nunez, S. C.; Garcez, A. S.; Garcez, E. M.; Baptista, A. (Research in Sports Medicine, 2022)
This study evaluates photobiomodulation (PBM) on cardio-respiratory function and swimming performance in parathletes. Ten swimming parathletes were tested before PBM, after PBM and placebo irradiation applied on upper musculature. After warmup, the parathletes rested for 1 min, and heart rate was recorded. Three sessions of 50 m free style swimming at maximum effort, with 5-min interval were performed and time, peak and recovery heart rate were recorded. After 1 week, biceps, deltoid, and trapezius received 108 J of energy from an LED array or sham-irradiation in a crossover study. After another week, the same protocol was repeated. All athletes improved time in 50ms swimming. On average, time decreased 4 s after PBM and 1.5 s after placebo. Also, the peak heartbeat was 10% lower after PBM. A muscular pre-conditioning using PBM with an infrared LED could modulate upper musculature and cardio-respiratory function, leading tobetter swimming performance in parathletes.